1997
DOI: 10.1046/j.1471-4159.1997.69020883.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Vulnerability of the CA1 and CA3 Subfields of the Hippocampus to Superoxide and Hydroxyl Radicals In Vitro

Abstract: Abstract:The relative roles of the superoxide and hydroxyl rad icals in oxidative stress-induced neuronal damage were investigated using organotypic hippocampal slice cultures. Cultures exposed to 100 ftM duroquinone, a superoxide-generating compound, for 3 h developed CAl -selective lesions over a period of 24 h. The damage accounted for '-64% of the CAl subfield, whereas CA3 showed just 6% damage, a pattern of damage comparable to that observed following hypoxia!ischaemia. Duroquinone-induced damage was atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 17 publications
7
87
1
4
Order By: Relevance
“…The acidosis following cerebral ischemia with enhancement of glial edema, protein denaturization, and depletion of energy generation creates an optimal milieu for free radical formation. 29,30) Oxidative stress is one trigger of apoptotic cell death, and treatment of cells with a variety of different exogenous antioxidants blocks apoptosis. 31) The mechanisms by which oxygen radicals are produced in apoptotic cells are still not clear, but disruptions in mitochondrial function may play a role.…”
Section: Fig 1 Representative Brain Infarctions After 1-h Ischemia/mentioning
confidence: 99%
“…The acidosis following cerebral ischemia with enhancement of glial edema, protein denaturization, and depletion of energy generation creates an optimal milieu for free radical formation. 29,30) Oxidative stress is one trigger of apoptotic cell death, and treatment of cells with a variety of different exogenous antioxidants blocks apoptosis. 31) The mechanisms by which oxygen radicals are produced in apoptotic cells are still not clear, but disruptions in mitochondrial function may play a role.…”
Section: Fig 1 Representative Brain Infarctions After 1-h Ischemia/mentioning
confidence: 99%
“…However, the mechanisms underlying this heterogeneous sensitivity are not well understood. Regional variability in hypoxic sensitivity has been reported in the brain during conditions of oxygen deprivation such as hypoxic ischemia, malonate-induced mitochondrial metabolic disruption (2), and during oxidant stress following ischemia (4). As an example of selective vulnerability within a well defined brain structure, the hippocampus contains two regions that clearly differ in their susceptibility to hypoxia.…”
Section: Expression Of Constitutively Active Akt In Pc-12 Cells Inducmentioning
confidence: 99%
“…However, the mechanisms underlying this heterogeneous sensitivity are not well understood. Heterotopic differences in hypoxic sensitivity are now well established in the brain during conditions of oxygen deprivation such as hypoxic ischemia and the oxidant stress that follows reperfusion or malonate-induced mitochondrial metabolic disruption (1)(2)(3)(4). Previous studies from our laboratory have identified significant differences in the hypoxic susceptibility of the CA1 and CA3 hippocampal regions, with CA1 vulnerability being particularly prominent in response to intermittent mild hypoxic episodes (5-7).…”
mentioning
confidence: 97%
“…Indeed, periods of hypoxia that are not fatal to other brain structures may nonetheless result in significant damage to the hippocampus. However, not all hippocampal areas exhibit the same degree of susceptibility to the ischemic injury, with the CA3 area showing greater resistance to ischemic damage compared with area CA1 (12). Accordingly, a brief period of global brain ischemia causes cell death in hippocampal CA1 pyramidal neurons 48-72 hours after reperfusion, with neuronal preservation in other hippocampal layers.…”
Section: Introductionmentioning
confidence: 99%